COVID-19 EM UMA CIDADE DO INTERIOR DO ESTADO DO ESPÍRITO SANTO, BRASIL - Aarão, Bruno Machado; Piassi, Filipe Faria; Pavoni, Gabrielle Alves Martins; de Faria, Matheus Henrique Silva; de Salles, Pedro Henrique Soares Pessanha; Pereira, Marcelo Cordeiro (Revista Científica da Faculdade de Medicina de Campos, 2020)
Sars-Cov-2 has been the subject of study in the most diverse medical fields, since the pandemic began in China in late 2019. According to the American College of Cardiology, individuals with comorbid conditions have a hospitalization rate of 50%, when affected by COVID-19. It is observed that patients with comorbidities, such as arterial hypertension and diabetes, in addition to elderly individuals, have a higher rate of hospitalization due to the infection of the new coronavirus, as well as the aforementioned case. In view of the current pandemic and a disease still under investigation, all information about the clinic, treatment, complementary exams and patient monitoring can generate better knowledge about the characteristics of the infection and the development of treatment protocols. Therefore, with pharmacological management still uncertain, the use of antivirals, such as Oseltamivir, anticoagulants and 3rd generation cephalopsorins, have created positive perspectives regarding the prognosis of patients infected with Sars-Cov-2. Therefore, with pharmacological management still uncertain, the use of antivirals, such as Oseltamivir, anticoagulants and 3rd generation cephalopsorins, have created positive perspectives regarding the prognosis of patients infected with Sars-Cov-2.